ANALISIS PENINGKATAN PARTISIPASI POLITIK MASYARAKAT DI WILAYAH KOTA JAKARTA TIMUR PADA PEMILIHAN PRESIDEN TAHUN 2019: Studi Kasus Masyarakat Di Wilayah Kelurahan Bambu Apus, Lubang Buaya dan Cipayung - Noni Anggraeni Taunu (2022)
The 2019 simultaneous elections are executive and legislative general elections. In history for the first time that simultaneous elections were held, the number of registered voters in the 2019 election increased more sharply than in the 2014 election. Specifically for the East Jakarta area, the number of participants who used their right to vote increased. Where in 2014 the participation rate reached 75% while in 2019 the number of users of voting rights increased by 5.46%. With this, it is known that the level of community participation in the East Jakarta area reached 80.46%. There are several interesting facts that are thought to influence the level of public participation in the 2019 general election, especially in the presidential election, including in the East Jakarta area. This research discusses what factors influence the increase in public participation in the 2019 presidential election in East Jakarta. With the aim of knowing the factors that influence increasing public participation in the 2019 presidential election in the City of East Jakarta, through community case studies in three Sub-Districts in the East Jakarta area namely, Bambu Apus, Lubang Buaya, and Cipayung. The research method used in this study is the Sequential Explanatory Mixed Methods (sequential mixed method). The results obtained in this study are that political arousal factors, personal characteristics, social characteristics, and political education are influential with different significance in encouraging an increase in the political participation of the people of East Jakarta in the 2019 presidential election.